BMP9 promotes methionine- and choline-deficient diet-induced nonalcoholic steatohepatitis in non-obese mice by enhancing NF-KB dependent macrophage polarization - Jiang, Qianqian; Li, Qi; Liu, Beibei; Li, Guixin; Riedemann, Gabriel; Gaitantzi, Haristi; Breitkopf-Heinlein, Katja; Zeng, Ajuan; Ding, Huiguo; Xu, Keshu (International immunopharmacology, 2021)
Our previous study confirmed that bone morphogenetic protein 9 (BMP9) participated in the development of nonalcoholic steatohepatitis (NASH) by affecting macrophage polarization. The focus of this study was to further confirm the role of macrophages in BMP9-mediated NASH and to analyze the underlying mechanism. In vivo, mice that were administered adeno-associated viral (AAV) vectors containing a null transgene (AAV-null) or the BMP9 transgene (AAV-BMP9) were divided into methionine- and choline-deficient (MCD) and control diet (CD) groups, and they were administered either control liposomes or clodronate liposomes via tail vein injection, the latter to deplete macrophages. The mice were sacrificed after 4 weeks of MCD diet feeding. In vitro, RAW264.7 cells were pretreated with or without BAY11-7085 (an NF-κB inhibitor) and stimulated with recombinant human BMP9 (rh-BMP9). To explore the underlying mechanism of action of BMP9, primary human monocyte-derived macrophages were additionally investigated and immunohistochemistry, biochemical assays, qRT-PCR, and Western blotting were used. The characteristics of NASH-related inflammation were assessed by hepatic histological analysis. Serum AST and ALT and hepatic triglyceride were examined by biochemical assays. We found that the expression of M1 macrophage genes (including CD86, IL1β, IL6, MCP-1 and TNFα) and the number of M1 macrophages (iNOS+ macrophages) in the liver were significantly elevated after BMP9 overexpression and BMP9 directly upregulated TLR4 expression in MCD-induced NASH. These effects were eliminated by macrophage depletion. In vitro, we discovered that BMP9 enhanced the nuclear translocation of NF-κB to induce macrophage M1 polarization in RAW264.7 cells and it promoted LPS-mediated activation of the NF-κB pathway in primary human macrophages. Taken together, this study demonstrates that BMP9 promotes NASH development by directly acting on macrophages.
Im Titel ist das K bei "NF-KB" tiefgestellt
Gesehen am 24.06.2022